Assessment irradiation effects on different development stages of Callosobruchus maculatus and on chemical, physical and microbiological quality of cowpea seeds. Issue 4 (31st August 2020) - Hammad, A.; Gabarty, A.; Zinhoum, R. A.
Abstract: Irradiation is a physical, environmentally friendly treatment which does not leave any residues in the product. It is increasingly used as an alternative to methyl bromide and other chemical fumigants for disinfestation of insect pest in stored grains. In this research, we try to evaluate the effect of low gamma irradiation doses in the range of 50–1200 Gy on the different stages of Callosobruchus maculatus . It was found that no adults emerged after irradiation of eggs at 450 Gy. No emerging adults (F1 generation) have been shown when larvae or pupae were exposed to 650 Gy. Also, no emerging adult has been shown from the parental C. maculatus adults irradiated with 650 Gy. When suppression of F1 generation was used for the measuring effective irradiation dose and phytosanitary efficacy, 650 Gy was required for disinfestation of cowpea seed weevils. The irradiation dose level of 650 Gy was used for the large-scale confirmatory tests applied to 27, 754 adults of C. maculatus in cowpea seeds resulting in non F1 adults' production with a confidence level of 93.77%. All the physical and chemical characteristics of cowpea seeds were non-significantly ( P ≤ 0.05) affected by the irradiation dose of 650 Gy. Meanwhile, this irradiation dose very slightly reduced the microbial load of cowpea seeds. We recommend the generic dose 650 Gy as the phytosanitary irradiation dose for the cowpea seed weevil.